Диндерде улут түшүнүгү - Зууридинов, Өскөнбай (Scientific Journal of Faculty of Theology, 2017)
There are two teories about origin of religions; first theory is the religion founded by man and second theory is homo religous. The best spritual moralty is religion. In this article written about national undastanding of all religions. The nation understanding of members of religions which based on the cult of ancestors are higher than following others. The world religions aren’t takes place an any national concepts but we saw that some ethnic groups are turned religions to national values.